Kebijakan Hilirisasi Nikel Indonesia dan Dampaknya pada Sengketa Perdagangan Internasional di World Trade Organization (WTO): Kasus Larangan Ekspor Bijih Nikel antara Uni Eropa dan Indonesia - Maya Iswandi (Jurnal Hukum Lex Generalis, 2025)
The Indonesian government's policy of nickel downstreaming aims to increase the added value of mineral commodities, particularly nickel, which is one of the strategic natural resources in Indonesia. As part of this effort, Indonesia imposed a ban on the export of nickel ore with a content below 1.7% starting from January 1, 2020, in order to encourage the development of smelters and enhance domestic industry capacity. This policy has contributed to an increase in the export of higher value-added nickel products, which significantly contributes to the national economy. However, the policy has led to a dispute with the European Union (EU), which filed a complaint at the World Trade Organization (WTO), arguing that the policy violated international trade rules under the General Agreement on Tariffs and Trade (GATT) 1994. The dispute process went through consultation, panel formation, and hearings, with the panel ultimately ruling that Indonesia was in violation of the GATT 1994 provisions. Indonesia filed an appeal, but the process has been delayed due to the lack of a functioning Appellate Body, which has yet to be established due to the United States' objections. This dispute illustrates the dynamics of international trade policy, testing whether Indonesia’s downstreaming policy can withstand international legal pressures and its impact on the domestic economy. This study aims to analyze the implications of Indonesia’s nickel downstreaming policy within the context of the WTO dispute and evaluate the challenges and opportunities faced by Indonesia in achieving national industrialization through mining downstreaming.